Minsk Narratives. An emerging learning biography in times of protest - Evans, Rob (Adult Education Discourses, 2022)
This paper will look at the rich narratives of a young Belarusian professional, Aleksandra, collected in audio and video narratives and interviews since the autumn and winter 2020-2021. By looking in detail at Aleksandra’s experiences of the 2020 movement for democracy in Belarus, the paper will try to illuminate the work done by Aleksandra to give sense to her self-narrative, and to locate the voice she has been looking for and may have found. Connecting the usual micro interactions of conversation-like talk to the complex spaces of political and social relations, biographical narratives constructed in this kind of interview talk become an important lens through which the ongoing construction of individual/social identities and the realignment of individual meaning–making in times of harsh biographical transition can be heard. Learning biographies, as narrative constructions, in which the layers of experience of a (being) lived life are drawn upon as resources, are situated in, and create, personalised storied spaces. Learning biographies draw upon biographical knowledge, which is the prerequisite for biographical reflexion, i.e. being able to think your own biography through anew and form it anew. In times when demands on people come as sudden and difficult, this type of knowledge serves as crucial biographical competence. The paper will show that such times of conflict entail redefinition of self, the re-drafting of biographies, the urgent need to reinvent the self in relation to others. Discursive processes hearable in such biographic narratives involve the changes imposed by civil conflict on narrators’ own and on others’ words, on their very narrative resources, altering radically the very language hitherto used to describe themselves and the world. They involve, too, the confrontation of past layers of experience with a difficult, yet sometimes exhilarating present. The construction of narratives of hope and solidarity can be observed. Finally, the paper explores the possibility of identifying in the interviews heard here the crucial relationships between everyday lives, the experience found in a widening of everyday sites of biographical experience, learning, and narration.